The association of vesicoureteric reflux and renal scarring, and their prevalence among Malay children in HUSM Kubang Kerian, Kelantan - Che Mohamed, Siti Kamariah; Yunus, Rohaizan; Harun, Juhara; BK, Das; Noor, Syed Hatim; Musa, Kamarul Imran (2007)
VUR is a known risk factor for pyelonephritis, and it is also known to be associated with renal scarring. This association is due to a combination of intrarenal reflux and bacteriuria. Prevalence of VUR and renal scarring varied among authors depending on the geographical region and different racial groups. The purpose of this study is to determine the prevalence of vesicoureteric reflux and renal scarring among Malay children with UTI who had undergone DMSA renal scan in HUSM. The association of renal scarring with VUR and other factors were also evaluated.